Cyclic plasticity of engineering materials : - Kang, Guozheng (John Wiley & Sons, Inc., 2017)
This book is an important reference for students, practicing engineers and researchers who study cyclic plasticity in the areas of mechanical, civil, nuclear, and aerospace engineering as well as materials science.